BAF complexes facilitate decatenation of DNA by topoisomerase IIα - Dykhuizen, Emily C.; Hargreaves, Diana C.; Miller, Erik L.; Cui, Kairong; Korshunov, Andrey; Kool, Marcel; Pfister, Stefan; Cho, Yoon-Jae; Zhao, Keji; Crabtree, Gerald R. (Nature, 2013)
Mutations in the subunits of BAF chromatin-remodelling complexes are frequently found in human cancer; here deletion of BAF subunits or expression of mutants of the ATPase subunit BRG1 attenuates genome-wide binding of topoisomerase IIα, resulting in tangled chromosomes, anaphase bridges and G2/M arrest.
Gesehen am 07.01.2021